MODELING OF THE INNOVATIVE POTENTIAL MANAGEMENT SYSTEM OF INTEGRATED AGRICULTURAL FORMATIONS OF THE MESO-ECONOMIC LEVEL - Kairova; Shokumova; Marzhokhov (Revista Inclusiones, 2020)
The aim of the study is to substantiate theoretical provisions and recommendations for the formation of an organizational and economic mechanism for managing the innovative potential of integrated agro-industrial formations on the basis of a conceptual model, taking into account the limitations associated with the management and production specifics of the internal organization of integrated agro-industrial formations. The methodological basis of the research is general scientific methods of analysis and synthesis, methods of scientific abstraction, the modeling method and theory and methodology of the systems approach.